2021
DOI: 10.1590/1414-431x2021e11183
|View full text |Cite
|
Sign up to set email alerts
|

Poricoic acid A induces apoptosis and autophagy in ovarian cancer via modulating the mTOR/p70s6k signaling axis

Abstract: Due to the high mortality and rapid disease progression, ovarian cancer remains one of the most common malignancies threatening the health of women. The present study was conducted to explore the anticancer effects and the underlying mechanisms of poricoic acid A (PAA), the main components of Poria cocos, on ovarian cancer. We investigated the anticancer effects of different concentrations of PAA in the SKOV3 cell line. Cell viability and proliferation were examined by CCK-8 assay. Cellular migration and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Also, the specific interaction between PAA and NF- κ B/MAPK signaling pathway required further investigation. Additionally, as a formulated drug, “ Poria cocos polysaccharide oral solution” was approved by the China Food and Drug Administration in 2015 for the treatment of various types of cancer, hepatitis, and other diseases, and “ Poria cocos polysaccharide oral solution” can be applied alone or during chemoradiation for the treatment of cancer [ 11 , 32 ]. Further improvement of the above experiments will be expected to provide strong support for PAA in the treatment of CRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the specific interaction between PAA and NF- κ B/MAPK signaling pathway required further investigation. Additionally, as a formulated drug, “ Poria cocos polysaccharide oral solution” was approved by the China Food and Drug Administration in 2015 for the treatment of various types of cancer, hepatitis, and other diseases, and “ Poria cocos polysaccharide oral solution” can be applied alone or during chemoradiation for the treatment of cancer [ 11 , 32 ]. Further improvement of the above experiments will be expected to provide strong support for PAA in the treatment of CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also revealed anticancer effects of PAA. For example, Ma et al found that PAA could inhibit the proliferation, migration, and invasion of ovarian cancer cells SKOV3 and induce apoptosis and autophagy of cancer cells [ 11 ]. In addition, PAA plays an important role in a variety of kidney-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…TS, WSP, and AP are the three major active ingredients in PC. For example, TS has been proven to exert potent pharmacological effects [ 3 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], such as anti-inflammatory, anti-tumor, and diuretic effects [ 6 , 7 , 8 ]. Polysaccharides have liver-protective, immune-boosting, and anti-aging effects [ 28 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent study showed that overexpression of the long-chain non-coding RNA H19 downregulated miR-140–5p and activated the PI3K/AKT signaling pathway to promote OC cell invasion, migration, and epithelial-mesenchymal transition ( Xu et al, 2021 ). Previous studies have found that poricoic acid A, the main component of Poria cocos , can induce apoptosis in ovarian cancer cells by regulating the mTOR/p70s6k signaling axis ( Ma et al, 2021 ). And our research has identified another important active component of Poria cocos , so we want to further explore the anticancer effect of tumulosic acid, and compare the effects of poricoic acid A with tumulosic acid.…”
Section: Discussionmentioning
confidence: 99%